Screening for suicide risk factors in prison inmates: evaluating the efficiency of the Depression, Hopelessness and Suicide Screening Form (DHS) - Mills, Jeremy F. (Legal and criminological psychology, 2005)
The Depression, Hopelessness and Suicide Screening Form (DHS; Mills & Kroner, 2002) is a recently developed self-report instrument to aid in screening inmates in the titled areas. Research has shown the DHS to have good internal consistency, factor structure and construct validity. The present study extends the previous validation research by comparing the disclosure of suicide risk factors on the DHS with both interview-based and file review information. In addition, the DHS scores were used to predict psychological distress. The results indicate that despite the paper-and-pencil self-report approach of the DHS it is comparably efficient in gathering suicide risk factors to other methods. In addition, the predictive accuracy of the DHS in identifying inmates experiencing psychological distress was confirmed. The current study has implications for the method of collection of suicide screening information. The discussion centres on the potential of self-report in screening for suicide and self-harm indicators in inmate populations.